PENGARUH KARAKTERISTIK MEREK, KARAKTERISTIK PERUSAHAAN DAN KARAKTERISTIK KONSUMEN MEREK TERHADAP KEPUASAN PELANGGAN WARUNG MAKAN NASI KULIT SYUURGA YOGYAKARTA - Mursyid Mursyid (Kajian Ekonomi dan Bisnis, 2022)
The research objectives to be obtained by researchers in this research are to determine 1) the effect of brand characteristics on customer satisfaction at Warung Makan Nasi Kulit Syuurga Yogyakarta; 2) the influence of company characteristics on customer satisfaction at Warung Nasi Kulit Syuurga Yogyakarta; 3) the influence of consumer brand characteristics on customer satisfaction at Warung Makan Nasi Kulit Syuurga Yogyakarta; and 4) the influence of brand characteristics, company characteristics and consumer brand characteristics on customer satisfaction at Warung Makan Nasi Kulit Syuurga Yogyakarta simultaneously. The results of the study concluded that 1) brand characteristics have an influence on customer satisfaction at Warung Makan Nasi Kulit Syuurga Yogyakarta; 2) company characteristics have an influence on customer satisfaction at Warung Makan Nasi Kulit Syuurga Yogyakarta; 3) the characteristics of Brand Consumers have an influence on customer satisfaction at Warung Makan Nasi Kulit Syuurga Yogyakarta; and 4) brand characteristics, company characteristics and brand consumer characteristics simultaneously have an influence on customer satisfaction at Warung Makan Nasi Kulit Syuurga Yogyakarta